Glaucoma, a silent thief of sight: Implication for social work intervention in the prevention of blindness in Nigeria. (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Glaucoma, often called the "silent thief of sight," is a leading cause of irreversible blindness worldwide, particularly in Nigeria, where its prevalence among adults over 40 is approximately 5.02%. The disease is insidious, progressing without noticeable symptoms until significant vision loss occurs. This poses a critical social challenge, as many individuals remain undiagnosed and untreated, with only about 10% receiving appropriate care. In Nigeria, the implications for social work intervention are profound. Social workers can play a pivotal rolein increasing awareness and understanding of glaucoma through targeted community outreach programs. By educating high-risk populations about the importance of regular eye examinations, social workers can facilitate early detection and intervention. Additionally, social workers can collaborate with eye care providers to improve access to eye care services, particularly in underserved areas. They can advocate for the integration of glaucoma screening into primary healthcare, ensuring that preventative measures are accessible to all. Support and counseling for diagnosed individuals are also essential, as social workers can help patients navigate their treatment options and adhere to prescribed care plans. Furthermore, by engaging with policymakers, social workers can address systemic barriers to eye care access, such as cost and availability. By harnessing their skills and resources, social workers can significantly contribute to the prevention of blindness from glaucoma in Nigeria, ultimately enhancing the quality of life for individuals at risk and fostering healthier communities.
Keywords: Glaucoma; Social work intervention; Eye care access; Community outreach; Blindness prevention